LINKING SOCIAL DRIVERS, WATER QUALITY, AND ECONOMIC VALUE IN FOREST FRAGMENTS SURROUNDING SPRINGS - Sugiarto, Michelle Talisia; Putri, Auralia Novriani; Sinaga, Felix Bintara Putra; Prijono, Sugeng; Sari, Rika Ratna; Saputra, Danny Dwi (JTSL (Jurnal Tanah dan Sumberdaya Lahan), 2026)
Spring ecosystems in forest fragments provide important environmental services, but their economic value is rarely included in management decisions. Most management efforts focus only on physical protection, while the way visitors value these ecosystems receives little attention. This study aims to estimate the economic value of spring ecosystem services and analyze the factors influencing visitors’ willingness to pay (WTP). This study also examines the relationship between WTP, water quality indicators, and differences in ecological conditions across several categories of forest fragments. Observations were conducted at sixteen spring locations in East Java, Indonesia. These locations represent large and small forest fragments and two management orientations, namely instrumental and relational. Data on the social and psychological characteristics of visitors were combined with several biophysical indicators, including water quality. Principal component analysis (PCA) was applied to analyze these variables, and economic efficiency was evaluated using an adjusted land equivalent ratio (LER). The results show that WTP is more influenced by visit experience, visitor trust in management, and perceived benefit efficiency than by basic demographic characteristics alone. Fragments with an instrumental orientation show higher economic efficiency compared to those with a relational orientation. Meanwhile, water quality in fragments with a relational orientation is much better, as indicated by high DO and TDS levels and greater and more stable discharge values. These findings indicate differences between economic performance and ecological conditions across forest fragment categories. Therefore, integrating social, ecological, and governance dimensions is essential for developing effective conservation strategies for springs in forest fragments.